Responses of phytoplankton community to eutrophication in Semerak Lagoon (Malaysia) - Er, Huey Hui; Lee, Li Keat; Lim, Zhen Fei; Teng, Sing Tung; Leaw, Chui Pin; Lim, Po Teen (Springer Verlag (Germany), 2018)
Effects of aquaculture activities on the environmental parameters and phytoplankton community structure were investigated in a semi-enclosed lagoon located at Semerak River, Malaysia. Elevated concentrations of phosphate and ammonia were observed at the aquaculture area and the inner lagoon. Relatively low dissolved oxygen, high total chlorophyll a, and high phytoplankton abundances but low species richness were recorded. Chaetoceros, Pseudo-nitzschia brasiliana, Blixaea quinquecornis, and Skeletonema blooms were observed, and some were associated with anoxia condition. Eutrophication level assessed by UNTRIX suggests that the water quality in the lagoon is deteriorating. Dissolved inorganic phosphorus and nitrogen at the impacted area were 15 and 12 times higher than the reference sites, respectively. Such trophic status indices could provide a useful guideline for optimal aquaculture management plan to reduce the environmental impact caused by aquaculture.